Dimensions of Women Migrant Workers’ Vulnerabilities Amidst Industrial Development and Pandemic’s Disruption - Yovi Arista; Zulyani Evi; Wahyu Susilo (Jurnal Perempuan, 2020)
Women migrant workers have a significant role and contribution in driving migration, economy, and global development. Behind the remittance flows, women migrant workers are still overshadowed by the threats of various problems. The dimensions of the problems faced are increasingly complex as the depletion of mobility limits between countries, the increasing of securitization policy as well as the rapid progress of global development in social, economic, and political aspects. Through the literature review, this article intends to highlight the vulnerability of Indonesian women migrant workers from the perspective of migration and governance froma feminist perspective. The results of the review show that women migrant workers are still facing multidimensional vulnerability. This includes the actual conditions of women migrant workers facing injustice, violations of rights, affected by disruption of information-technology, and being center in the pandemic crisis. This condition also leads to the structural aspects related to protection’s policy and institutional issues that are not sensitive to the interests and the root of problems faced by women migrant workers.